Seed productivity of lily sorts (Lilium L.) of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine collection - L.M. Kykot; O.D. Tymchenko; O.M. Len (Інтродукція Рослин, 2006)
The results of study of seed productivity at free pollination without castration of flowers of Lilium × hort. of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine collection are given. It's determined, that the overwhelming majority of sorts (72,7%) are fructiferous and to form high-grade seeds, and consequently can be used as the parent forms at realization of selection works.